The Diploma Divide - Healy, Elizabeth (Colloquium: The Political Science Journal of Boston College, 2025)
This paper uses political behavior to support the argument that affirmative action is still necessary in today’s culture to create more tolerant campuses, and in turn, a more tolerant American population. The sunset provision in previous Supreme Court cases, such as Bakke and Grutter, demonstrates that affirmative action should not be a forever policy, but is necessary in order to provide opportunities to students of all backgrounds and ultimately strive towards the American ideal of equality. Studies have shown that the more educated a person is, the more likely they are to be more tolerant of people outside of their own in-group due to social learning theory, contact theory, and increased levels of personal efficacy. Data also shows that this tolerance is enduring over a lifetime. The so-called “diploma divide” can also be explained by the aftermath of attending a university.